Ongoing activation of sphingosine 1-phosphate receptors mediates maturation of exosomal multivesicular endosomes - Kajimoto, Taketoshi; Okada, Taro; Miya, Satoshi; Zhang, Lifang; Nakamura, Shun-ichi (Nature communications, 2013)
During late endosome maturation, cargo molecules are sorted into intralumenal vesicles (ILVs) of multivesicular endosomes (MVEs), and are either delivered to lysosomes for degradation or fused with the plasma membranes for exosome release. The mechanism underlying formation of exosomal ILVs and cargo sorting into ILVs destined for exosome release is still unclear. Here we show that inhibitory G protein (Gi)-coupled sphingosine 1-phosphate (S1P) receptors regulate exosomal MVE maturation. Gi-coupled S1P receptors on MVEs are constitutively activated through a constant supply of S1P via autocrine activation within organelles. We also found that the continuous activation of Gi-coupled S1P receptors on MVEs is essential for cargo sorting into ILVs destined for exosome release. Our results reveal a mechanism underlying ESCRT-independent maturation of exosomal MVEs. Exosomes originate from inward budding of the endosomal membrane followed by cargo sorting, and are released from the cell by fusion of the endosome with the plasma membrane. Kajimoto et al. show that the cargo sorting process depends on continuous local activation of endosomal sphingosine 1-phosphate receptors.